The Vbeta13 T Cell Receptor Monoclonal Antibody Reduces Hyaluronan and CD68+, CD3+, and CD8+ Cell Infiltrations to Delay Diabetes in Congenic BB DRLyp/Lyp Rats - Bogdani, Marika; Faxius, Linda; Fex, Malin; Ramelius, Anita; Wernersson, Anya; Mordes, John P.; Blankenhorn, Elizabeth P.; Lernmark, Åke (Frontiers in Endocrinology, 2021)
The depleting Vβ13a T cell receptor monoclonal antibody (mAb) 17D5 prevents both induced and spontaneous autoimmune diabetes in BB rats. Here it was tested in congenic DRLyp/Lyp rats, all of which spontaneously developed diabetes. Starting at 40 days of age, rats were injected once weekly with either saline, His42 Vβ16 mAb, or 17D5 mAb and monitored for hyperglycemia. Diabetes occurred in 100% (n = 5/5) of saline-treated rats (median age, 66 days; range 55–73), and in 100% (n = 6/6) of His42-treated rats (median age, 69 days; range 59–69). Diabetes occurred in fewer (n = 8/11, 73%) 17D5-treated rats at a later age (median 76 days, range 60–92). Three (27%) of the 17D5-treated rats were killed at 101–103 days of age without diabetes (17D5 no-diabetes rats). Survival analysis demonstrated that 17D5 mAb delayed diabetes onset. Saline- and His42-treated rats had severely distorted islets with substantial loss of insulin-positive cells. These rats exhibited prominent hyaluronan (HA) staining, with the intra-islet HA+ accumulations measuring 5,000 ± 2,400 µm2 and occupying 36 ± 12% of islet area, and severe (grade 4) insulitis with abundant infiltration by CD68+, CD3+, and CD8+ cells. The 17D5 mAb-treated rats with delayed diabetes onset exhibited less severe insulitis (predominantly grade 3). In contrast, the 17D5 no-diabetes rats had mostly normal islets, with insulin+ cells representing 76 ± 3% of islet cells. In these rats, the islet HA deposits were significantly smaller than in the diabetic rats; the intra-islet HA+ areas were 1,200 ± 300 µm2 and accounted for 8 ± 1% of islet area. Also, islet-associated CD68+ and CD3+ cells occurred less frequently (on average in 60 and 3% of the islets, respectively) than in the diabetes rats (present in >95% of the islets). No CD8+ cells were detected in islets in all 17D5 no-diabetes rats. We conclude that mAb 17D5 delayed diabetes in DRLyp/Lyp rats and markedly reduced expression of HA and concomitant infiltration of CD68+, CD3+, and CD8+ cells. Our findings underscore the importance of refining immune suppression in prevention or intervention clinical trials to use mAb reagents that are directed against specific T cell receptors.